2005
DOI: 10.1007/s10438-005-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermostabilities of plant phenol oxidase and peroxidase determining the technology of their use in the food industry

Abstract: Stabilities of phenol oxidase and peroxidase from tea plant ( Camellia sinensis L.) clone Kolkhida leaves, apple ( Mallus domestica L.) cultivar Kekhura fruits, walnut ( Juglans regia L.) green pericarp, and horseradish ( Armoracia lapathifolia Gilib) roots were studied using different storage temperature modes and storage duration. It was demonstrated that both enzymes retained residual activities ( ~10% ) upon 20-min incubation at 80 ° C. Phenol oxidases from tea, walnut, and especially apple, as well as tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Very early work suggested that ''polyatomic phenol oxidase'' activity in walnut hulls produced a germicidal fluid that could inhibit bacterial growth (Cook et al, 1911). More recent studies have described the thermostability and basic biochemical properties of PPO activity in walnut hull extracts (Mchedlishvili et al, 2005;Piffaut and Metche, 1991). Overall, however, very little is known about the biochemistry and molecular biology of PPOs in walnut.…”
mentioning
confidence: 99%
“…Very early work suggested that ''polyatomic phenol oxidase'' activity in walnut hulls produced a germicidal fluid that could inhibit bacterial growth (Cook et al, 1911). More recent studies have described the thermostability and basic biochemical properties of PPO activity in walnut hull extracts (Mchedlishvili et al, 2005;Piffaut and Metche, 1991). Overall, however, very little is known about the biochemistry and molecular biology of PPOs in walnut.…”
mentioning
confidence: 99%
“…Recent proteomics studies confirm that malting barley cultivar variation in peroxidase isozyme spatio-temporal profiles might affect the colour and clarity of the wort, and probably the beer, and play a role in the metabolism of oxygen during mashing 94 . Different ways to control the undesirable activity of peroxidases during brewing have been suggested 109,126 .…”
Section: Beer Colloidal Stabilitymentioning
confidence: 99%
“…Cultivar variation in barley seed peroxidase isozyme spatio-temporal profiles might affect beer quality 8,9,177 . Beer turbidity during storage could perhaps be prevented using natural inhibitors of these enzymes 212 . Seed-specific peroxidases from cereals appear to be important allergens in hypersensitive diseases associated with the manipulation of flour 19,292 .…”
Section: Peroxidases (Pr-9)mentioning
confidence: 99%